THE HEALTH BENEFITS OF FERMENTED FOOD: A NARRATIVE REVIEW - Mohd Kamalul Abrar, Nabil Husaini; Md Jaffri, Juliana (Malaysian Journal of Science, 2023)
Fermented foods are consumed in many parts of the world since ancient times and they include dairy products, meat, fruits, vegetables, and alcoholic beverages. These foods have been documented to be beneficial to human health due to the microbial content, which mainly consists of probiotics of various bacterial and fungal species. Fermented food probiotics can modulate gastrointestinal health, thereby affecting other bodily systems such as the immune system and brain functions. The microbial and nutritional content of fermented foods may also contribute to reducing cardiovascular risks and improving metabolic syndrome parameters. Fermented foods have antimicrobial properties that can aid in suppressing the growth of pathogenic microbes. In addition, fermented foods may impart beneficial effects to the nervous system, which include improvement of cognitive function and a decrease in the symptoms of depression, anxiety, and stress. Literature relating to the benefit of fermented foods on different aspects of human health is sparse which poses significant limitations on understanding the relationship between fermenting foods and human health. This paper describes different types of fermented foods containing the relevant micro-organisms associated with the improvement of several health conditions.